Stenosing Tenosynovitis Due to Excessive Texting in an Adolescent Girl: A Case Report - Johnson, Jason D.; Gaspar, Michael P.; Shin, Eon K. (Journal of Hand and Microsurgery, 2016)
We present a case report of stenosing tenosynovitis of the flexor pollicis longus tendon in an adolescent girl who required surgical release after failing conservative measures. The patient had no other risk factors, aside from her excessive texting, which we postulate led to her condition. Although there have been a few reports of tendinitis and tenosynovitis secondary to texting, we believe this is the first in the literature to report trigger thumb requiring surgical release in an adolescent.
Keywords: stenosing tenosynovitis; trigger thumb; adolescent; texting; teenager